2012
DOI: 10.1002/mus.22315
|View full text |Cite
|
Sign up to set email alerts
|

Intermuscular relationship of human muscle fiber type proportions: Slow leg muscles predict slow neck muscles

Abstract: We suggest the existence of an across-muscle phenotype with respect to fiber type proportions; some individuals display generally faster muscles and some individuals slower muscles when compared with others.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
27
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 54 publications
0
27
1
2
Order By: Relevance
“…Whether possessing the right MFTC is due to the genetic aspect, rather than the effect of training has been subject of extensive investigation. Vikne et al (2012) suggested the existence of an across- muscle phenotype, supporting the importance of the heritability component. In our study, we could confirm a significant positive correlation between the carnosine Z-scores in the leg and the carnosine Z-scores of the arm muscles.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Whether possessing the right MFTC is due to the genetic aspect, rather than the effect of training has been subject of extensive investigation. Vikne et al (2012) suggested the existence of an across- muscle phenotype, supporting the importance of the heritability component. In our study, we could confirm a significant positive correlation between the carnosine Z-scores in the leg and the carnosine Z-scores of the arm muscles.…”
Section: Discussionmentioning
confidence: 88%
“…Vikne et al. () suggested the existence of an across‐muscle phenotype, supporting the importance of the heritability component. In our study, we could confirm a significant positive correlation between the carnosine Z ‐scores in the leg and the carnosine Z ‐scores of the arm muscles.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, the result from an uncontrolled, cross-sectional study of participants with neck pain of various etiologies on the contrary indicates a possible, minor increase in the fast fiber type direction [47]. Also, the reported type 1 fiber proportion in the neck muscles from the participants with post-traumatic etiology in the study of Uhlig [47] is almost identical to that found in presumably healthy participants [48]. Thus, it seems that the most reasonable explanation for the altered kinematics in the WAD participants would be the muscle activation patterns.…”
Section: Discussionmentioning
confidence: 95%
“…It is well known that fiber proportions vary between different muscles in humans (and other species;Johnson, Polgar, Weightman, & Appleton, 1973). A recent article by Vikne, Gundersen, Liestøl, Maehlen, and Vøllestad (2011) showed that those expressing a relatively large proportion of Type I fibers in one muscle also express a relatively large proportion of these fibers in other muscles. Although more evidence is needed, sampling just one muscle in all subjects may still be a valuable indicator of overall relative fiber proportion.…”
mentioning
confidence: 99%